Heart Failure: From Research to Clinical Practice Volume 3 (Advances in Internal Medicine,, 2018)
"Heart Failure: From Research to Clinical Practice" contains chapters that describe the current views on the biological mechanisms, clinical assessment, diagnosis and evidence-based treatments of the condition. Topics in this volume range from basic research at cell and molecular level to patient care in everyday clinical practice and provide essential background information and analyses of recent advances for a deeper understanding of the issues involved. With contributions from international experts in their specified fields and are suitable for both beginners and more advanced readers. This volume includes not only the essential information for clinical practice but also the latest information from the contemporary guidelines and the recommendations from leading societies. It also covers ongoing research and puts forward new hypotheses that can be tested in future research. This comprehensive volume will provide a valuable resource for both research students and expert clinicians.